TEACHERS' SENSE OF SELF-EFFICACY, ENGLISH PROFICIENCY, AND TEACHING ABILITY IN EFL SETTING: A CASE STUDY IN TERTIARY LEVEL - Dwita Laksmita Rachmawati; Dian Fadhilawati (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2020)
One important character which should be owned by teacher that influence the outcome of teacher is called as teacher self – efficacy. However, the correlation between teacher’ self – efficacy and linguistic proficiency hasn’t really investigated yet. Hence, this research aims to examine the connection between language proficiency to their efficacy perceptions. The participants of this research were 11 teachers of private University in Indonesia with various demographic characteristics. They were asked to answer related to the Teacher Efficacy Scale (TES) and recognize their linguistic proficiency self – rating. The statistical analyzing result which used Pearson – product moment correlation and Regression analysis showed a signification correlation between teacher’s self – efficacy and their proficiency level. The regression results also affirmed that the possibility level of proficiency of self – efficacy beliefs of teachers in classroom activity. The findings of this research are elaborated in relation to the previous research.